Opioid users with comorbid hepatitis C spent more time in agonist therapy: A 6-year observational study in Taiwan. (September 2017) - Chen, Horng-Maw; Lu, Tsung-Hsueh; Chang, Kun-Chia; Lee, Kuan-Ying; Cheng, Ching-Ming
Abstract: Background: Hepatitis C virus (HCV) infection is highly prevalent among opioid agonist therapy (OAT) patients, but little is known about long-term OAT use among this population. Methods: Subjects diagnosed as opioid dependence were recruited from Mar. 2006 to Jul. 2008 in a psychiatry center in southern Taiwan with the OAT censored in 2012, and their socio-demographics, drug use characteristics, and markers of blood-borne infection were assessed at entry. Correlates with HCV infection and OAT retention were analyzed by multivariate logistic regression. Retention (OAT utilization) was defined as the in-treatment period of OAT during the 6-year observation period. Results: A total of 983 patients (88.3% men) were included. The prevalences of HCV and HIV infection were 91.4% and 17.9%, respectively. The mean duration of OAT during the study period was 2.3 ± 0.8 years. Significant correlates with HCV infection were retention of at least three years in OAT (AOR: 4.24, 95%CI: 1.49–12.03), ever sharing injection equipment (AOR: 227.04, 95%CI: 57.22–900.87), not living with family (AOR: 5.54, 95%CI: 1.45–21.16), lower educational attainment (AOR: 2.10, 95%CI: 1.15–3.82) and previous drug offense (AOR: 6.35, 95%CI: 1.69–23.83). Significant correlates with retention were HCV infection (AOR: 2.53, 95%CI: 1.30–4.93) and divorced or separation in marriage (AOR: 0.65, 95%CI: 0.44–0.96). Conclusions: This six-year observational study revealed a better retention in OAT if opioid-dependent individuals had comorbid hepatitis C. This provided opportunities for OAT patients with HCV infection to obtain medical treatment while staying in an OAT program. Further research could explore the possibility of eradicating comorbid HCV infection among these long-term treatment cases. Highlights: The prevalences of HCV and HIV infection were 91.4% and 17.9%, respectively. The mean duration of OAT was 2.3 years during a six-year period in Taiwan. Retention in OAT was better if comorbid HCV infection existed over three years. Lower educational attainment was significantly associated with HCV infection. Divorced or separation in marriage tended to interrupt retention in OAT.